PELUANG PENINGKATAN PRODUKTIVITAS DAN DAYA SAING LADA Opportunity For Increasing Productivity And Competitiveness Of Pepper - Siswanto, Siswanto; Ardana, I Ketut; Karmawati, Elna (Perspektif, 2020)
Pepper is a spice commodity that plays an important role in the Indonesian economy, and occupies the first position as an export commodity for the spice plant commodity. In the last few decades the volume and value of exports of pepper has decreased, so that Indonesia's position as the world's largest producer and exporter was shifted by Vietnam. In addition to a decrease in area, the national average productivity of pepper is still low (<1000 kg / ha / year) compared to other world pepper producing countries. Pepper cultivation technology innovation is needed to increase the productivity and competitiveness of Indonesian pepper in the world. Three main components that affect the increase in productivity and competitiveness of pepper, namely the use of seed technology, cultivation efficiency, and efficiency of pepper processing. Pepper seed technology includes the use of superior varieties and preparation of superior quality and healthy seeds. Until now, 10 high-yielding varieties have been produced with an average productivity of> 3.0 tonnes / ha and quality seed propagation technology, but the performance of seedlings has not been running well, due to limited information and adequate number of seeds. Pepper cultivation technology that is environmentally friendly and efficient starting from seed preparation, land, planting, maintenance, pruning, fertilization, pest control and harvesting has been produced. Likewise, more efficient yield processing technology using appropriate equipment and certain enzymes for soaking, threshing, stripping, drying and sorting has been produced. However, in the field there are still many farmers who have not applied them or are not consistent in fully applying existing technology so that the results obtained are not optimal. Therefore it is necessary to encourage efforts to develop and supervise the implementation of SOPs appropriately and consistently so that the productivity, quality and competitiveness of pepper can be improved.ABSTRAKLada merupakan komoditas rempah yang berperan penting dalam perekonomian Indonesia, dan menduduki posisi pertama sebagai komoditas ekspor komoditas tanaman rempah. Dalam beberapa dasawarsa terakhir volume dan nilai ekspor lada mengalami penurunan, sehingga posisi Indonesia sebagai produsen dan exportir terbesar dunia sempat tergeser oleh Vietnam.Â  Selain terjadinya penurunan luas areal, produktivitas rata-rata nasional lada tergolong masih rendah (<1000 kg/ha/th) dibandingkan negara produsen lada dunia lainnya. Inovasi teknologi budidaya lada sangat diperlukan untuk meningkatkan produktivitas dan daya saing lada Indonesia di dunia. Tiga komponen utama yang berpengaruh terhadap peningkatan produktivitas dan daya saing lada, yaitu pemanfaatan teknologi perbenihan, efisiensi budidaya, dan efisiensi pengolahan lada. Teknologi perbenihan lada meliputi penggunaan varietas unggul dan penyiapan benih unggul bermutu dan sehat. Hingga saat ini telah dihasilkan 10 varietas unggul dengan produktivitas rata-rata > 3,0 t/ha serta teknologi perbanyakan benih bermutu, namun kinerja perbenihan belum berjalan baik, karena keterbatasan informasi dan jumlah benih bina. Teknologi budidaya lada yang ramah lingkungan dan efisien mulai dari persiapan benih, lahan, penanaman, pemeliharaan, pemangkasan, pemupukan, pengendalian hama penyakit hingga panen sudah dihasilkan. Teknologi pengolahan hasil yang lebih efisien menggunakan peralatan yang tepat guna dan pemanfaatan enzim tertentu untuk perendaman, perontokan, pengupasan, pengeringan dan sortasi telah dihasilkan. Namun di lapangan masih banyak ditemukan petani yang belum mengaplikasikannya atau tidak konsisten mengaplikasikan teknologi yang ada secara penuh sehingga hasil yang diperoleh kurang baik.Â  Oleh karena itu perlu didorong upaya pembinaan dan pengawasan terhadap penerapan SOP secara tepat dan konsisten agar produktivitas, mutu dan daya saing lada dapat ditingkatkan.